FACTORS ASSOCIATED WITH SELF-REPORTED USER ACCEPTANCE AND PERCEIVED USEFULNESS OF SI-TELUR PETIS: A CROSS-SECTIONAL STUDY - Mei Rianita Elfrida Sinaga; Indrayanti; Santy Ercelina Nainggolan; Retno Heru Setyorini; Sulistiyani; Ontran Sumantri Riyanto; Endang Khoirunnisa (International Archives of Medical Sciences and Public Health, 2026)
Non-communicable diseases (NCDs) such as hypertension and diabetes mellitus are major contributors to global mortality. Mobile health (mHealth) applications are increasingly utilized for preventive efforts, yet research often prioritizes usability over actual effectiveness. Si-Telur Petis is a telenursing application developed in Indonesia to support behavioral modification and NCD prevention. This study explores factors influencing the effectiveness of Si-Telur Petis in preventing hypertension and diabetes mellitus. A total of 109 working-age individuals (15–59 years) in Yogyakarta, Indonesia, participated in the study. Effectiveness was assessed using a validated 33-item questionnaire (Cronbach’s alpha = 0.957) based on the Unified Theory of Acceptance and Use of Technology (UTAUT), examining predisposing, enabling, reinforcing, system quality, safety, and satisfaction factors. Results show that employment status, enabling factors, system quality, safety, and satisfaction significantly affect effectiveness, with satisfaction emerging as the strongest predictor (?=0.867, p<0.001). These findings indicate that user satisfaction is the key determinant of Si-Telur Petis effectiveness, emphasizing the importance of user-centered design, reliable system quality, and robust security in mHealth adoption. Despite limitations in sample size and geographic scope, this study offers preliminary evidence supporting the broader implementation of digital nursing interventions.